2020
DOI: 10.1111/aji.13344
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein inhibits FURIN‐MT1‐MMP‐mediated invasion of ectopic endometrial stromal cells in endometriosis possibly by reducing the secretion of TGFB1

Abstract: Problem: Endometriosis (EMs) is characterized by the presence of endometrial stroma and glands outside the uterus. Our previous study showed that baicalein inhibited proliferation and induced apoptosis in EMs. However, the effects of baicalein on the invasiveness of ectopic endometrial stromal cells (EcESCs) remain unclear. The aim of this study was to assess the potential anti-invasive effect of baicalein and determine the underlying mechanism. Methods: The invasive and migratory properties of EcESCs were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Our previous studies have shown that baicalein induces EcESCs apoptosis and inhibits invasion [ 19 , 20 ]. We intended to explore more mechanisms of baicalein as a potential anti-ferroptosis drug in Ems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that baicalein induces EcESCs apoptosis and inhibits invasion [ 19 , 20 ]. We intended to explore more mechanisms of baicalein as a potential anti-ferroptosis drug in Ems.…”
Section: Discussionmentioning
confidence: 99%
“…Baicalein also inhibits erastin-induced ferrous iron production, glutathione depletion, and lipid peroxidation in pancreatic cancer cells [ 16 ]. Our previous studies had shown that baicalein induced EcESCs apoptosis through the NF-kB signaling pathway [ 19 ] and inhibited the invasion of EcESCs by invasion-related proteins, including MT1-MMP, MMP2, and MMP9 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total furin activity in cervical swabs and uterine lavage correlated with the severity and progression of atypical endometrial hyperplasia and endometriosis 10,30 . An experimental study illustrated that inhibition growth of endometriosis by baicalein reduced furin level 52 . The results imply the possible function of PC furin in the propagation of atypical endometrial hyperplasia and endometriosis.…”
Section: Furin and Tumor Progressionmentioning
confidence: 94%
“…The number of cells in the G1 phase increased with a simultaneous decline in the number of cells in the S and G2/M phases compared with non-treated control cells [ 95 ]. More recent findings indicate that baicalein reduces ectopic endometrial stromal cell invasiveness, as demonstrated by analysis of invasion-related proteins, including MMP-9, MMP-2 and membrane type 1-matrix metalloproteinase (MT1-MMP) [ 96 ]. In a mouse model of endometriosis, intraperitoneal administration of baicalein inhibited ectopic lesions’ growth, reduced MT1-MMP, proprotein convertase of MMPs (FURIN) and TGFB1 expression.…”
Section: Potential Of Polyphenol Compounds In Endometriosis Managementmentioning
confidence: 99%
“…In a mouse model of endometriosis, intraperitoneal administration of baicalein inhibited ectopic lesions’ growth, reduced MT1-MMP, proprotein convertase of MMPs (FURIN) and TGFB1 expression. Thus, baicalein with a potent pro-apoptotic and anti-invasive activity may provide a novel treatment strategy for endometriosis, as the authors suggested [ 96 ]. Promising preclinical research results indicate that undertaking clinical studies on endometriosis treatment with baicalein is warranted and recommended to obtain strong evidence for therapeutic baicalein potential.…”
Section: Potential Of Polyphenol Compounds In Endometriosis Managementmentioning
confidence: 99%